Pengaruh Suhu dan Waktu Ekstraksi Terhadap 6-(Dimethylnitroryl)-4,4- Diphenyl-3-Heptanone dan 9,12- Octadecadionic Acid (Z,Z)-, Methyl Ester pada Limbah Rambut Jagung (Zea Mays L.) - Wahyusi, Kindriari Nurma; Triadira, Aurriel Sekar; Nur , Shiva Eric Zulfikar (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Corn silk, a part of the maize plant that plays a role in pollination, is often considered agricultural waste and has not been optimally utilized. However, it contains bioactive compounds with potential antimicrobial properties. The main problem addressed in this study is the underutilization of corn silk as a source of valuable bioactive compounds, particularly flavonoids and alkaloids, which can be developed for health-related applications. This research aims to investigate the effect of extraction temperature and time variations on the levels of flavonoid compound 9,12-Octadecadionic Acid (Z,Z)-, Methyl Ester and alkaloid compound 6-(Dimethylnitroryl)-4,4-Diphenyl-3-Heptanone in corn silk extract. The method used was maceration with 80% ethanol as the solvent, followed by analysis to determine the optimum conditions. The results showed that the optimum condition for 6-(Dimethylnitroryl)-4,4-Diphenyl-3-Heptanone was achieved at 50°C for 5 hours, yielding a concentration of 21.57%. Meanwhile, the optimum condition for 9,12-Octadecadionic Acid (Z,Z)-, Methyl Ester was obtained at 40°C for 5 hours, with a concentration of 21.62%. These findings indicate that corn silk has promising potential as a source of bioactive compounds, offering added value for agricultural waste utilization. Furthermore, this study provides implications for the development of corn silk–based products with economic and health benefits.